(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Outdoor thermal discomfort in commercial districts presents a critical challenge in tropical urban environments, where elevated air temperatures and intense solar radiation limit the usability and comfort of open spaces. This study evaluates the effectiveness of Urban Heat Island (UHI) mitigation strategies in enhancing outdoor thermal comfort within a commercial district through ENVI-met simulations. Four intervention scenarios were developed and compared against existing conditions, encompassing structural-based, vegetation-based, surface material–based, and integrated approaches. Simulations were conducted for the hottest day of the dry season, with thermal comfort assessed at pedestrian height (1.4 m) using the Physiological Equivalent Temperature (PET) index. Structural interventions produced an average PET reduction of 1.24 K, demonstrating localized cooling effects, whereas vegetation-oriented strategies achieved the most substantial improvement, reducing average PET by up to 3.91 K. In contrast, material-based interventions exhibited the least efficacy, yielding a maximum average PET reduction of only 0.32 K and even contributing to increased PET during daytime hours due to reflected solar radiation. The combined intervention scenario delivered a more balanced outcome, with average PET reductions reaching 2.60 K. Despite these interventions, PET values largely remained within the “very hot” category, underscoring the necessity for radiation-sensitive urban design approaches that prioritize vegetation-centric mitigation strategies.